Pengaruh Pendapatan Asli Daerah, Belanja Modal Terhadap Pertumbuhan Ekonomi dan Dana Perimbangan Sebagai Pemoderasi di Kabupaten/Kota Sumatera Utara - Hutapea, Ruth Septaria (Jurnal Manajemen Akuntansi (JUMSI), 2023)
This study aims to analyze the influence of Regional Original Income (PAD) and capital spending on economic growth in the District/City of North Sumatra. In addition, this study also analyzes the role of balancing funds as a moderator in the relationship between PAD, capital spending, and economic growth in the regions. The data used in this study is secondary data obtained from the financial reports of the local government and the Central Bureau of Statistics (BPS) of North Sumatra from 2011 to 2020. Data analysis uses panel regression with a fixed effect. The results of the study show that PAD has a significant positive effect on economic growth in the districts/cities of North Sumatra. This shows that the higher the PAD, the better the economic growth in the area. In addition, capital expenditure also has a significant positive effect on economic growth, which indicates that the greater the capital expenditure made by the regional government, the better the economic growth in the region. In the context of the role of balancing funds, research results show that balancing funds can moderate the relationship between PAD and economic growth. When the balancing funds received by the regions are greater, the positive influence of PAD on economic growth will increase. In addition, balancing funds can also moderate the relationship between capital spending and economic growth. When the balancing fund gets bigger, the positive effect of capital spending on economic growth also increases.